ENFORCEMENT OF THE LAW OF THE SEA AND THE ROLE OF THE NAVY IN ENSURING INDONESIA'S SOVEREIGNTY IN THE EXCLUSIVE ECONOMIC ZONE (ZEE) - Danardono; Manggala, Bayu Suryadi; Tampubolon, Vernandito Sudharta Raftua; Siregar, Adhito Martogi Natanael; Triadi, Irwan (Journal Social Sciences and Humanioran Review, 2024)
As the largest archipelago with vast marine territory, Indonesia bears great responsibility in maintaining maritime security and sovereignty. The challenges faced include transnational crimes such as illegal fishing, smuggling of goods and drugs, as well as the threat of terrorism and piracy. Therefore, the national defence and security system, especially at sea, must be a priority. The Navy has a major role in maintaining territorial integrity, enforcing the law, and protecting the country from various threats. This research uses the normative juridical method, which examines the existence of jurisdictional law by adopting a historical perspective and involving various sources such as journal articles and legal commentaries. To maintain the sovereignty and security of territorial waters, Indonesia needs a strong maritime defence system. Law enforcement in the Zona Ekonomi Eksklusif (ZEE) is crucial to maintaining sovereignty over Indonesia's marine natural resources. This research aims to examine Indonesia's great responsibility in maintaining maritime security and sovereignty as the largest archipelago and analyse the main role of the Indonesian Navy in maintaining territorial integrity and enforcing the law in Indonesian waters.